Integrating Formal Methods with Informal Digital Hardware Development - Evans, Neil (Electronic Communications of the EASST, 2011)
This paper presents some results from an industrial project to develop high-integrity digital hardware by integrating formal methods with a more traditional informal approach. The ultimate goal of the project team was to produce sythesisable VHDL that could be proven to meet given requirements for an embedded controller. The burden was on the formal methods experts to integrate themselves into the team. This paper describes the formal approach that was developed as a result.